Physiological role of AMP-activated protein kinase (AMPK): insights from knockout mouse models. (1st February 2003) - Viollet, B.; Andreelli, F.; Jørgensen, S.B.; Perrin, C.; Flamez, D.; Mu, J.; Wojtaszewski, J.F.P.; Schuit, F.C.; Birnbaum, M.; Richter, E.; Burcelin, R.; Vaulont, S.
Abstract : AMP-activated protein kinase (AMPK) is viewed as a fuel sensor for glucose and lipid metabolism. To understand better the physiological role of the catalytic AMPK subunit isoforms, we generated two knockout mouse models with the α1 (AMPKα1 −/− ) and α2 (AMPKα2 −/− ) catalytic subunit genes deleted. No defect in glucose homoeostasis was observed in AMPKα1 −/− mice. On the other hand, AMPKα2 −/− mice presented high plasma glucose levels and low plasma insulin concentrations in the fed period and during the glucose tolerance test. Nevertheless, in isolated AMPKα2 −/− pancreatic islets, glucose-stimulated insulin secretion was not affected. Surprisingly, AMPKα2 −/− mice were insulin-resistant and had reduced muscle glycogen synthesis as assessed in vivo by the hyperinsulinaemic euglycaemic clamp procedure. Reduction of insulin sensitivity and glycogen synthesis were not dependent on the lack of AMPK in skeletal muscle, since mice expressing a dominant inhibitory mutant of AMPK in skeletal muscle were not affected and since insulin-stimulated glucose transport in incubated muscles in vitro was normal in AMPKα2 −/− muscles. Furthermore, AMPKα2 −/− mice have a higher sympathetic tone, as shown by increased catecholamine urinary excretion. Increased adrenergic tone could explain both decreased insulin secretion and insulin resistance observed in vivo in AMPKα2 −/− mice. We suggest that the α2 catalytic subunit of AMPK plays a major role as a fuel sensor by modulating the activity of the autonomous nervous system in vivo .